Lending a hand: perceptions of green credit cards. Issue 7 (1st October 2018) - Huang, Lei; Fitzpatrick, Julie
Abstract : Purpose: The purpose of this paper is to explore the impact of donation amount and framing on financial products, this research investigates consumers' attitudes and behaviors toward cause-related credit cards with different donation sizes and framing types. Design/methodology/approach: This research investigates consumers' perceptions of green credit cards using two experiments with a between-subject design ( n =297) and a mixed design ( n =238), respectively. All the participants, recruited from a major state university in the USA, are undergraduate students who use credit cards. Findings: A medium-size donation optimizes the outcome of a cause-related credit card offer. Moreover, a donation framed as cash rewards has stronger effects on a consumer's perception and consequent reactions to the "green" credit cards than an annual percentage rate framing. Finally, consumers with high levels of environmental concern and propensity to volunteer have stronger intention to adopt and are more likely to recommend the proposed credit card. Originality/value: Building upon the theories of social exchange and symbolic interaction, this research is the first to provide empirical evidence regarding the application of volunteerism and perceived consumer effectiveness for financial institutions and their cause-related marketing campaign partners in selecting suitable environmental causes.